Water‐soluble derivatives of 4‐oxo‐N‐(4‐hydroxyphenyl) retinamide: synthesis and biological activity. (6th June 2016) - Musso, Loana; Tiberio, Paola; Appierto, Valentina; Cincinelli, Raffaella; Cavadini, Elena; Cleris, Loredana; Daidone, Maria Grazia; Dallavalle, Sabrina
Abstract : A novel series of 4‐oxo‐ N ‐(4‐hydroxyphenyl) retinamide (4‐oxo‐4‐HPR) derivatives were synthesized with the aim of increasing the poor solubility of the parent compound in biological fluids, while maintaining the cytotoxic activity and the dual mechanism of action. The most promising compound13a showed antiproliferative/apoptotic activity. The analysis of its mechanism of action revealed that it retained the particular characteristic of 4‐oxo‐4‐HPR which is able to induce cell cycle arrest during the mitotic phase, coupled with the formation of aberrant mitotic spindles. Abstract : Replacement of the carbonyl group of 4‐oxo‐4‐HPR led to a novel class of water‐soluble derivatives that maintained the efficacy and the dual mechanism of action of the parent compound.